Absenteeism-Related Wage Loss Associated With Multimorbidity Among Employed Adults in the United States. Issue 6 (June 2021) - Mohamed, Rowida; Patel, Jayeshkumar; Shaikh, Nazneen Fatima; Sambamoorthi, Usha
Abstract : Objective: To estimate the incremental absenteeism-related wage loss associated with multimorbidity and examine the influence of paid sick leave policy (PSLP) on multimorbidity-associated absenteeism wage loss. Methods: We used the Medical Expenditure Panel Survey (MEPS) 2015 data. Two-part generalized linear models (GLM) were employed, using binomial distribution and gamma distribution with a log link. Results: Nationally, multimorbidity was associated with a 9 billion incremental absenteeism-related wage loss annually among working adults. Absenteeism-related wage loss was higher among those with multimorbidity than those without multimorbidity. The incremental annual absenteeism-related wage loss associated with multimorbidity was lower in settings that offered paid sick leave than that did not offer paid sick leaves. Conclusion: Multimorbidity is associated with higher absenteeism-related wage loss. Paid sick leave policies can reduce the impact of multimorbidity on absenteeism-related wage loss. Abstract : Supplemental Digital Content is available in the text